2015
DOI: 10.1039/c5ra16062f
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional asynchronous spectrum with auxiliary cross peaks in probing intermolecular interactions

Abstract: A new approach called "asynchronous spectrum with auxiliary peaks (ASAP)" is proposed for generating 2D asynchronous spectrum to investigate intermolecular interaction between two solutes (P and Q) dissolved in the same solutions. In the ASAP approach, a virtual substance S with an isolated peak assumed to be at v S is introduced, while the characteristic peaks of P and Q are actually observed at v P and v Q . The concentrations series of P, Q and S are specifically designed so that spectral portion that has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 65 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…2DCOS can be used to simplify spectra by spreading peaks that are overcrowded in 1D spectra along the second spectral dimension. Over the past three decades, a large number of research studies regarding 2DCOS have been reported, since 2DCOS can be applied to diverse sample systems under the influence of a number of perturbations and probed by many different spectroscopic tools. The above results demonstrate that 2DCOS is a powerful spectral resolution enhanced technique that can be used to analyze highly congested bands. Many subtle spectral features that are not visible in 1D spectra can be visualized as cross peaks in 2D correlation spectra.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…2DCOS can be used to simplify spectra by spreading peaks that are overcrowded in 1D spectra along the second spectral dimension. Over the past three decades, a large number of research studies regarding 2DCOS have been reported, since 2DCOS can be applied to diverse sample systems under the influence of a number of perturbations and probed by many different spectroscopic tools. The above results demonstrate that 2DCOS is a powerful spectral resolution enhanced technique that can be used to analyze highly congested bands. Many subtle spectral features that are not visible in 1D spectra can be visualized as cross peaks in 2D correlation spectra.…”
Section: Introductionmentioning
confidence: 87%
“…In our previous work, we have developed OSD ( o rthogonal s ample d esign), DOSD ( d ouble o rthogonal s ample d esign), AOSD ( a synchronous o rthogonal s ample d esign), DAOSD ( d ouble a synchronous o rthogonal s ample d esign), and others , to characterize intermolecular interactions between solutes dissolved in the same solutions. In these approaches, the occurrence of cross peaks in 2D spectra can be used as an unambiguous evidence of the existence of an intermolecular interaction.…”
Section: Introductionmentioning
confidence: 99%
“…These were used to perform perturbation domain decomposition 16,17 (PDD) and, more recently, to probe intermolecular interactions. 18 In this work, we introduce the MuSCA technique and demonstrate its utility in combination with k -means clustering. 1921 We start with a carefully chosen synthetic data set and thereafter we apply it to measured Raman spectra obtained from cell aggregates obtained by the directed differentiation of human embryonic stem cells (hESCs) toward pancreatic insulin-producing cells.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] We developed an orthogonal sample design scheme and related techniques to investigate intermolecular interaction between two solutes dissolved in the same solutions. [22][23][24][25][26] Via these approaches, an intermolecular interaction is reliably reflected as cross-peaks in 2D spectra. Furthermore, the pattern of cross-peaks can reflect a subtle variation on peak position and bandwidth, as well as absorptivity relevant to intermolecular interaction.…”
Section: Introductionmentioning
confidence: 99%